Automation Establishment Mold Set Image Database Mouldbase By Utilizing Standard: Automation Establishment Mold Set Image Database Mouldbase By Utilizing Standard - Edi Junaedi AC (Jurnal Mantik, 2020)
Research related to the design process is increasingly gaining attention so extensive and intensive research community. It is based on the fact that the increasing challenges that arise from the consumer is a trigger among practitioners in the manufacturing world meet their diverse needs. The proper integration of all activities of the design using a computer (Computer Aided Design) and all manufacturing activities paced computer (Computer Aided Manufacture) is a key factor in creating a manufacturing environment that is totally integrated with the computer as a tool primarily, particularly manufacturing activities mold (Computer Mold Integrated Manufacturing), this research has been done. The overall aim is to achieve global optimization of an enterprise by integrating the use of computers in all areas of production, especially in producing mold as a component that will produce a variety of products that will be used directly by the end-user. This study specifically sought to develop an interface or software that is able to assist a designer in designing a mold (mold). Especially in preparing various types of standard molds to automate the process of selecting and describing the various sets the desired mold. The resulting standard mold to be formed in accordance with a predetermined design shape and satisfy consumer desires. This research has been done, also an integral part of various other studies were conducted at the Laboratory of Production Systems Department of Industrial Engineering ITB. Implementation of the test results have shown that the software has been developed from the model in this study could be implemented and integrated with some software that has been developed previously.